Evaluation of the institutional climate and the teaching performance in the educational institutions of the primary level of the network N ° 11 of the district of Villa María del Triunfo. Lima Region 2016 - Bellido Corpus, Elizabeth (2020)
The research that has been carried out is quantitative, transversal, bivariate, basic. We use a non-experimental causal correlational design. Where the factors of study the two factors institutional atmosphere and instructor execution in "the primary level of the Network N ° 11 of the district of Villa María del Triunfo, Lima region 2016." The population is made up of 12 I.E of the primary level of 500 teachers and the sample constituted by 150 teachers from 8 educational institutions. In the data collection, two questionnaires were designed: the variable of institutional atmosphere variable instructing execution. The instruments come to fulfill the qualities of reliability and validity. The study has as a research hypothesis that there is a "significant relationship between the institutional climate and the teaching performance at the primary level of Network N ° 11 of the district of Villa María del Triunfo, Lima Region 2016". The results reject the null hypothesis and accept the alternative hypothesis, as observed in the statistics of the study groups, with a level of significance of 5%, there being statistical evidence to affirm that the performance of teaching is related to the institutional climate , since Spearman's Rho correlation results in 0.850, which is considered "very good". Therefore, the null hypothesis is rejected and the "significant relationship between the institutional climate and the performance of teaching at the primary level of Network No. 11 of the district of Villa María del Triunfo, Lima 2016 region" is rejected.